2018
DOI: 10.1192/bjp.2018.129
|View full text |Cite
|
Sign up to set email alerts
|

Cultural engagement and cognitive reserve: museum attendance and dementia incidence over a 10-year period

Abstract: SummaryTheories of cognitive reserve, disuse syndrome and stress have suggested that activities that are mentally engaging, enjoyable and socially interactive could be protective against the development of dementia. Using data from the English Longitudinal Study of Ageing, this study shows that for adults aged 50 and older visiting museums every few months or more was associated with a lower incidence rate of dementia over a 10-year follow-up period compared with less-frequent visiting. This association was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 16 publications
3
78
0
1
Order By: Relevance
“…Targeting non-optimal activities may in part explain the limited efficacy of current randomized-controlled trials (RCTs) on cognitive and neural outcomes [14,15]. A small number of epidemiological studies have begun to probe more activity-specific associations, suggesting that not all activities equally contribute to the risk of cognitive impairment [16][17][18].…”
mentioning
confidence: 99%
“…Targeting non-optimal activities may in part explain the limited efficacy of current randomized-controlled trials (RCTs) on cognitive and neural outcomes [14,15]. A small number of epidemiological studies have begun to probe more activity-specific associations, suggesting that not all activities equally contribute to the risk of cognitive impairment [16][17][18].…”
mentioning
confidence: 99%
“…Maintaining cognitive skills during museum visits was also associated with a lower incidence rate of dementia, reported in a cohort study over ten years 15 . This study also reinforces the finding that cultural engagement was associated with lesser social isolation.…”
Section: Figure 2 Infographic Of Terms Used In Articlesmentioning
confidence: 80%
“…In the analysis of the objectives and methodological designs, it was found that the publications were conducted exclusively with an older population (n=5) or groups of adults and older adults (n=7). In this case, five studies included people older than 45 years [5][6][7]12,15 and two considered younger people 4,10 . In articles with adult and older adult participants, age did not interfere with the results achieved.…”
Section: Figure 2 Infographic Of Terms Used In Articlesmentioning
confidence: 99%
See 2 more Smart Citations